1986
DOI: 10.1002/jso.2930330413
|View full text |Cite
|
Sign up to set email alerts
|

Primary teratocarcinoma of the lung

Abstract: Presented is the ninth reported case of teratocarcinoma arising from the parenchyma of the lung. Treatment should include wide surgical resection and adjuvant chemotherapy. Postoperative radiation therapy should be utilized if there is residual disease or nodal metastasis. Preoperative radiation therapy should be considered if there is evidence of chest wall involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A positron emission tomography G erm cell tumors are mostly encountered within the gonads or along the middle line in the mediastinum, retroperitoneum, sacral area, and skull basis, with the anterosuperior compartment of the mediastinum being the commonest location for extragonadal tumors. 1 Germ cell tumors of choriocarcinomatous or other nonseminomatous lineage that have allegedly risen into the lung have been rarely described, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and yolk sac tumor (YST) has usually been reported as one component of mixed germ cell tumors. 2,8,[10][11][12][13][14][15] Pure YST primary to the lung or pleura are exceptional events, with only very few cases reported in the English literature.…”
Section: Case Reportmentioning
confidence: 99%
“…A positron emission tomography G erm cell tumors are mostly encountered within the gonads or along the middle line in the mediastinum, retroperitoneum, sacral area, and skull basis, with the anterosuperior compartment of the mediastinum being the commonest location for extragonadal tumors. 1 Germ cell tumors of choriocarcinomatous or other nonseminomatous lineage that have allegedly risen into the lung have been rarely described, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and yolk sac tumor (YST) has usually been reported as one component of mixed germ cell tumors. 2,8,[10][11][12][13][14][15] Pure YST primary to the lung or pleura are exceptional events, with only very few cases reported in the English literature.…”
Section: Case Reportmentioning
confidence: 99%
“…Morgan et al [2], in 1992, reported a case and reviewed 30 literature cases. To their list, five more cases reported prior to 1992 but not included in their review should be added [5][6][7][8][9]. In 1993 Suzuki et al [10] reported two cases of benign pulmonary teratoma and cited 25 cases, including five cases with malignancy, in the Japanese literature.…”
Section: Discussionmentioning
confidence: 98%
“…Li ke teratoma of the mediastinum , intrap 비 monary teratoma is thought to originate from the third pharyngeal pouch which is the anlage of the thymus (5,6) . It has two forms in relation to p 비 monary architecture , parenchymal and endobronchial.…”
Section: Discussionmentioning
confidence: 99%
“…Most of intrapulmonary teratomas were parenchymal , and only four cases of endobronchial teratoma have been reported (5 , 6) . Approximately half of the intrapulmonary teratomas were located in the left upper lobe, the reason of which is not clearly understood (6). These tumors have been said to have malignant potential , and approximately one -third have been reported to be malignant teratomas (5 , 6) .…”
Section: Discussionmentioning
confidence: 99%